A Survey of the Parameters of the Friction Stir Welding Process of Aluminum Alloys 6xxx Series - Essa, Meshal; Alhajri, Fahad Salem (Engineering International, 2021)
Friction stir welding is a modern innovation in the welding processes technology, there are ‎several ways in which this technology has to be investigated in order to refine and make it ‎economically responsible. Aluminum alloys have strong mechanical properties when they are ‎welded by using the Friction Stir welding. Therefore, certain parameters of the welding ‎process need to be examined to achieve the required mechanical properties. In this project, a ‎literature survey has been performed about the friction stir welding process and its parameters ‎for 6xxx series aluminum alloys‎.
Keywords: Friction stir welding; welding ‎process; aluminum alloys; mechanical properties